The Effect of Slow Deep Breathing on Blood Pressure of Hypertension Patients in M. Djamil Hospital Padang 2018 - Neini Ikbal, R; Permata Sari, R (KnE Life Sciences, 2019)
The incidence of hypertension reached 50% of the total population in the world and is expected to increase to 64.01% by 2025. West Sumatra Province has a high incidence of hypertension, one of which is based on data from M. Djamil Hospital Padang, obtained 24,782 people suffering from hypertension in 2016. Handling hypertension with the aim of lowering blood pressure can be done in various ways, one of which is by non-pharmacological therapy, slow deep breathing. The purpose of the study is to determine the effect of slow deep breathing on blood pressure. The type of research was quasi-experiment with two groups, pre-test and post-test. The research was carried out in the Interne Room in M. Djamil Hospital Padang from February to August 2018. The population is all patients with hypertension in the interne room. The sampling technique used was purposive sampling and the number of samples was 28 people with criteria for hypertension samples, aged 40-60 years and not obese. Data processing is carried out computerizedly by processing the data using the Wilcoxon test. The results showed that there was an effect of slow deep breathing on systolic blood pressure in the intervention group with p = 0.01 and diastolic p = 0.02 and there was no effect of slow deep breathing on systolic blood pressure in the control group with p = 0.107 and diastolic p = 0.157. Keywords: slow deep breathing, blood pressure, hypertension